Produtividade da forragem de milho e Capim-marandu integrados em sistema agrossilvipastoril com eucalipto - Domingues, Miguel Sales [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective was to evaluate the development, light interception and chlorophyll content index of maize intercropped with marandu grass, the productivity of maize forage intercropped with marandu grass and development, light interception, chlorophyll content index and productivity of marandu grass intercropped or not with maize in an agrosilvopastoral system. The experiment was conducted at APTA - Andradina, SP and treatments were no eucalyptus (full sun: control) systems with eucalyptus (one and three rows) and within these five distances from trees (2, 4, 6, 8 and 10 m). Between strips eucalyptus was used integration with marandu grass with or without maize. Were evaluated in maize: plant height, ear height, chlorophyll content index, light interception, dry matter, fresh and dry matter forage. In grass tillering, height, chlorophyll content index, light interception and productivity of dry matter were evaluated. The experimental design was a randomized block in factorial arrangement with additional treatment (control) and four repetitions. The productivity of maize forage, dry matter, plant height, ear height were not influenced by the arrangements of trees. At a distance of 2 m from the trees had lower productivity, dry matter, plant height and ear height. Was difference between the values of light interception in maize distances between the first two evaluations. The heights during the development of maize were not affected by distance, or by arrangements of trees and there was no difference between the control and the agrosilvopastoral systems. Chlorophyll content index maize was not affected by distances from trees, or by arrangements and no difference between the control and the agrosilvopastoral systems. The height of the grass at distances from trees was lower in the first two evaluations. The light interception of the grass was shorter distance of 2 m from the trees in the last evaluation

O objetivo do trabalho foi avaliar o desenvolvimento, interceptação luminosa e índice de conteúdo de clorofila do milho consorciado com capim marandu, a produtividade de forragem do milho consorciado com capim- marandu e o desenvolvimento, interceptação luminosa, índice de conteúdo de clorofila e produtividade do capim-marandu consorciado ou não com o milho em sistema agrossilvipastoril. O experimento foi conduzido na APTA - Andradina, SP e os tratamentos foram sem eucalipto (controle), sistemas com eucalipto (1 e 3 linhas) e dentro destes, cinco distâncias em relação às árvores (2, 4, 6, 8 e 10 m). Entre as faixas de eucalipto foi utilizado o sistema de integração com o capim-marandu consorciado ou não com a cultura do milho. Foram avaliados no milho: altura de planta, altura de inserção de espiga, índice de conteúdo de clorofila (ICC), interceptação luminosa, produtividade de forragem na massa verde e seca e teor de matéria seca. No capim foram avaliados o perfilhamento, altura, ICC, interceptação luminosa e produtividade de massa seca. O delineamento experimental foi em blocos casualizados em arranjo fatorial com tratamento adicional (controle) e 4 repetições. A produtividade da forragem de milho, matéria seca, altura das plantas na colheita e altura de inserção de espiga não foram influenciadas pelos arranjos de árvores. À distância de 2 m em relação às árvores apresentou menores valores de produtividade, matéria seca, altura na colheita e altura de inserção de espiga. Houve diferença entre os valores de interceptação luminosa no milho entre as distâncias nas duas primeiras avaliações. As alturas durante o desenvolvimento do milho não foram afetadas pelas distâncias, nem pelos arranjos de árvores e não houve diferença entre o tratamento controle e os sistemas agrossilvipastoris. O ICC do milho não foi influenciado pelas distâncias em relação...
Keywords: Plantas forrageiras; Agrosilvicultura; Produtividade agrícola; Milho - Cultivo; Eucalipto - Cultivo